PENGARUH DANA PIHAK KETIGA, SPREAD BAGI HASIL, TINGKAT BAGI HASIL DAN NON PERFORMING FINANCING TERHADAP VOLUME PEMBIAYAAN BERBASIS BAGI HASIL ( STUDI KASUS BANK UMUM SYARIAH PERIODE 2017-2019 ) - alimaini, meriani; Dalimunte, Ahmad Amin; Nasution, Juliana (Fakultas Ekonomi Bisnis Islam, 2023)
This research is intended to determine and analyze the influence of Third Party Funds (DPK), Profit Sharing Spread (SBH), Profit Sharing Level (TBH), and Non Performing Financing (NPF) on the Volume of Profit Sharing Based Financing (PBH) of Sharia Commercial Banks. This research takes thebackground that the movements of PBH, DPK, SBH, TBH and NPF experience fluctuating movements from year to year. This research is quantitative in nature with secondary data sources, namely the quarterly financial balance reports of Sharia Commercial Banks starting in 2017-2019. Using multiple linear regression test as an analysis tool using SPSS 15.0. The conclusions in this study show that firstly, simultaneously, namely DPK, SBH, TBH and NPF have a significant effect on PBH. Second, separately or partially, DPK has a significant effect on PBH of Sharia Commercial Banks with a calculated t value of 22.040. Third, SBH has a significant effect on PBH with a calculated t value of 3.534. fourth, TBH has no effect on PBH at Sharia Commercial Banks with a calculated t value of -0.220. Fifth, NPF has no effect on PBH of Sharia Commercial Banks with a calculated t value of -0.1567